Review of the effects of coal properties and activation parameters on activated carbon production and quality - Spencer, William; Senanayake, Gamini; Altarawneh, Mohammednoor; Ibana, Don; Nikoloski, Aleksandar N. (Minerals engineering, 2024)
Activated carbon (AC) products are valuable for adsorption applications due to their high internal pore volume, surface area, surface functionality and strong adsorbent properties, which allow the capture of various ions and impurities in many applications, including precious metals recovery, water treatment, and gas purification. This review found that most of the world's AC is derived from bituminous and sub-bituminous coal, but low-rank coals are more suitable for AC production due to their higher reactivity to activation and increased porosity compared to high-rank coals. Coal-based AC is preferred for adsorption due to its surface functionality, porous structure, lower cost, suitability for single-use without reactivation, and the potential for regeneration. A positive correlation between carbonisation temperature and BET (Brunauer-Emmett-Teller) surface area and the impact of KOH and NaOH percentages on AC yield and surface area is identified. AC production, quality and yield are affected by coal type, rank, particle size, chemical composition, and process conditions such as activation method, activation temperature, and pre- and post-treatment steps. Properties of AC, such as surface area and iodine number, are higher in chemically activated carbon than in thermally activated carbon. The sustainable use of ilmenite/iron oxide activation yields AC suitable for water treatment due to its high iodine content. Low-rank coals, including those with high ash content, could be utilised with green collectors or gravity separation to minimise ash content.